Low Dietary Soy Isoflavonoids Increase Hippocampal Spine Synapse Density in Ovariectomized Rats - MacLusky, Neil J. (Brain Res, 2017)
High dietary intake of plant estrogens (phytoestrogens) can affect brain structure and function. The effects of phytoestrogen intake within the range of normal animal and human dietary consumption, however, remain uncertain. The aim of the present study was to determine the effects of the isoflavonoids present in a standard low phytoestrogen laboratory rat chow on spine synapse density in the stratum radiatum of area CA1 of the hippocampus. Weanling rats (22 days old) were fed either standard chow (Teklad 2018), a nutritionally comparable diet without soy (Teklad 2016) or a custom diet containing Teklad 2016 supplemented with the principal soy isoflavonoids, daidzein and genistein, for 40 days. Rats were ovariectomized at 54 days of age. Eight days later, spine synapse density on the apical dendrites of hippocampal pyramidal neurons in the stratum radiatum of area CA1 was measured by electron microscopic stereological analysis. Animals maintained on Teklad 2016 exhibited an approximately 60% lower CA1 spine synapse density than animals consuming Teklad 2018. Replacing genistein and daidzein in Teklad 2016 returned synapse density to levels indistinguishable from those in animals on Teklad 2018. These results indicate that the isoflavonoids in a standard laboratory rat diet exert significant effects on spine synapse density in the CA1 region of the hippocampus. Since changes in spine synapse density in this region of the hippocampus have been linked to cognitive performance and mood state, these data suggest that even relatively low daily consumption of soy phytoestrogens may be sufficient to influence hippocampal function.